2022
DOI: 10.1038/s41467-022-32147-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic actuation enhances transport and extends therapeutic lifespan in an implantable drug delivery platform

Abstract: Fibrous capsule (FC) formation, secondary to the foreign body response (FBR), impedes molecular transport and is detrimental to the long-term efficacy of implantable drug delivery devices, especially when tunable, temporal control is necessary. We report the development of an implantable mechanotherapeutic drug delivery platform to mitigate and overcome this host immune response using two distinct, yet synergistic soft robotic strategies. Firstly, daily intermittent actuation (cycling at 1 Hz for 5 minutes eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…Soft robotics represents a particularly useful technology in this context, with the potential to gently and minimally invasively interact with soft tissues. Our laboratory has already shown the ability to alter biomechanical properties at an implant site by reducing fibrotic capsule formation using intermittent soft robotic actuation ( 1 , 18 ). We recently demonstrated that such mechanotherapy significantly improved drug delivery, resulting in near-complete preservation of implanted device–mediated drug delivery in a mouse model over an 8-week period ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Soft robotics represents a particularly useful technology in this context, with the potential to gently and minimally invasively interact with soft tissues. Our laboratory has already shown the ability to alter biomechanical properties at an implant site by reducing fibrotic capsule formation using intermittent soft robotic actuation ( 1 , 18 ). We recently demonstrated that such mechanotherapy significantly improved drug delivery, resulting in near-complete preservation of implanted device–mediated drug delivery in a mouse model over an 8-week period ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has already shown the ability to alter biomechanical properties at an implant site by reducing fibrotic capsule formation using intermittent soft robotic actuation ( 1 , 18 ). We recently demonstrated that such mechanotherapy significantly improved drug delivery, resulting in near-complete preservation of implanted device–mediated drug delivery in a mouse model over an 8-week period ( 18 ). This technique can also increase mass transport and therapeutic effect via on-demand actuations that enable rapid release of a large bolus of drug, even in the presence of the fibrotic capsule ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations